1973
DOI: 10.1007/bf00021565
|View full text |Cite
|
Sign up to set email alerts
|

A note on Xanthomonas blight of beans (Phaseolus vulgaris (L.) savi) and prospects for its control by breeding for tolerance

Abstract: This short review attempts to collect information on Xanthomonas pathogens of beans that is of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1974
1974
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Reference to other sources of tolerance, found by different workers, is presented by HILL et al, (1972). LEAKEY (1973) recently presented an excellent detailed review of sources of tolerance to X. phaseoli. Germplasm sources used in our investigations are only reported here.…”
Section: Sourcesoftolerantgermplasmmentioning
confidence: 99%
“…Reference to other sources of tolerance, found by different workers, is presented by HILL et al, (1972). LEAKEY (1973) recently presented an excellent detailed review of sources of tolerance to X. phaseoli. Germplasm sources used in our investigations are only reported here.…”
Section: Sourcesoftolerantgermplasmmentioning
confidence: 99%
“…STARR and BURK., is a serious disease of Phaseolus vulgaris dry bean types. The importance and distribution of this disease is discussed in reviews by ZAUMEYER & THOMAS (1957) and by LEAKEY(1973). SAETTLER (1972) was not successful in controlling the disease by chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…New sources of tolerance to X. phuseoli have been identified by COYNE et al (1963COYNE et al ( , 1973 and numerous sources of tolerance have been reviewed by Leakey (1973). Recently SCHUSTER et al (1973) found that P. vulgaris PI 207262 (Colombia) dry bean had high tolerance to virulent strains from Uganda, Colombia, and the United States, while Great Northern (GN) Nebraska 1, sel.…”
Section: Introductionmentioning
confidence: 99%
“…Conforme algumas pesquisas, os genótipos PI 163117, PI 175829, PI 175858 (Coyne & Schuster, 1973a), PI 197687 (Coyne et al, 1963Coyne & Schuster, 1973b;Leakey, 1973) e Xan 161 (Scott & Michaels, 1992;Torres, 1996) foram considerados resistentes e o Xan 160 (Scott & Michaels, 1992) …”
Section: Resultsunclassified